Climate change as a risk to human security: a systematic literature review focusing on vulnerable countries of Africa - causes and adaptation strategies. (3rd April 2023) - Saraiva, Artur; Monteiro, Ana
The main purpose of this research is to systematically review the literature to understand how climate change influences stability and human security. The results identified from the bibliometric analysis allowed the identification of four dominant themes in the literature explaining the climate change and human security nexus: 1) food security related to agricultural systems; 2) water security associated with water scarcity and management; 3) humanitarian crises, emphasising conflict and climate migration; 4) adaptation and mitigation strategies. The results underline the ineffectiveness of current responses to climate change, suggesting the urgency of action to reduce its impact on communities most prone to the effects, particularly in fragile states in Sub-Saharan Africa. The study highlights some recommendations to policy and institutional leaders for a sustainable adaptation at the social, ecological, and economic dimensions. Additionally, this paper provides a theoretical contribution by explaining the nexus of climate change, human security, and conflict, proposing a new dimension for the concept of human security - ecological security.